Preliminary study of waste-delivered biosorbents to remove nutrients from rice mill wastewater - Uduwarage, U.D.T.M.; Devaisy, S. (university of Jaffna, 2020)
The objective of this study was to compare the performance of waste derived biosorbents - rice hull and peanut hull in removing nutrients from rice mill wastewater. Batch adsorption experiments were conducted for both biosorbents separately for varying doses (0 6 g/L) and contact times (0 300 min) under uniform experimental conditions to determine the optimum dosage and optimum contact time respectively. The efficiencies of the biosorbents were tested in terms of removal (%) of nitrates and phosphates from wastewater. Results revealed, the rice hull and the peanut hull do significantly remove nutrients from the wastewater (p value<0.05). The optimum doses of rice hull and peanut hull were 3 g/L and 4 g/L respectively, and the optimum contact time were 120 mins and 180 mins at their optimum doses and shaking of 150 rpm.
Keywords: Biosorbents; Peanut hull; Rice hull; Rice mill; Wastewater